Risky income or lumpy investments? Evidence on two theories of under-specialization - Ajay Shenoy (University of California, Economics Department, 2014)
Why do the poor have so many economic activities? According to one theory the poor do not specialize because relying on one income source is risky. I test the theory by measuring the response of Thai rice farmers to conditional volatility in the international rice price. Households expecting a harvest take on 1 extra activity when the volatility rises by 21 percent. I confirm the decrease in specialization costs households foregone revenue. I find no evidence to back a second theory in which households under-specialize because they cannot afford lumpy business investments.
Keywords: D13; O12; 330; risk; specialization; occupation; rice; Thailand